Religion and integration: religious organisations’ communication in a diverse city district of Oslo, Norway - Holte, Bjørn Hallstein (Journal of contemporary religion, 2020)
This article raises the question whether and how religious organisations contribute to integration in a diverse city district of Oslo, the capital of Norway. Drawing on Niklas Luhmann’s theory of society and his work on religion, it argues that this question requires an analysis of the way religious organisations are integrated into different social systems and of the way people are included in such organisations. With regard to the inclusion of people, the article suggests that not more than half of the city district’s population were members of local religious organisations and that the religious organisations may not have targeted excluded groups, as Luhmann suggests they might. Focusing on the way the religious organisations were integrated into different social systems, the article finds that they were engaged in local communities within the city district, with local public authorities and welfare service providers, and in religious networks that spanned the city, the country, and the world. The article concludes that the religious organisations in the city district were part of a global religious system and mostly communicated in non-religious ways at the local level. The contribution of religious organisations to integration must thus be understood in relation to communication on a global scale and across the secular/religious divide.